Structural configurations of thin dried polyaniline films on gold(111) from scanning tunneling microscopy - Vela, María Elena (1996)
The early stages of growth of polyaniline films electrodeposited on Au were studied by conventional electrochemical techniques, X-ray diffraction and ex situ scanning tunneling microscopy (STM). From high resolution STM imaging it appears that the first step of polyaniline formation involves the adsorption of aniline monomers on Au(111) terraces leading to domains with hexagonal arrays involving a phenyl-phenyl distance in the range 0.70 nm ⩽ d ⩽ 1.0 nm. The second step corresponds to the initiation of the polymer growth yielding typically 10 × 10 nm2 crystalline domains consisting of either 0.45 × 0.6 nm2 rectangular arrays or 0.75 × 0.45 nm2 arrays forming 120 ° angles. The crystalline domains coexist with highly disordered polymer domains. At advanced stages of growth, the formation of polymer fibers 2 nm in average width takes place leading to a full substrate coverage by a polymer deposit with an irregular surface.